IMPLEMENTATION OF GITOPS IN CONTAINERIZED INFRASTRUCTURE - Rayhan Gusty Alif; Lulu Chaerani Munggaran (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
IT Infrastructure is one of the core components of a business’ scalability and reliability, thus having an efficient way on managing the IT Infrastructure would be one of the core decisions for a business. IT Infrastructure itself has evolved throughout the years, with the rise of virtualization technology, containerization became more relevant as ever, one such example is Containerization Infrastructure, an IT Infrastructure that uses Containerization as its backbone. With the push of the technology, a new way of managing Containerization Infrastructure efficiently is needed. There are multiple researches regarding the implementation of GitOps already, but none of them explained the connection between GitOps and Containerized Infrastructure, this paper is intended to discuss the connection by implementing GitOps in a Containerized infrastructure. This resulted in a quite steep learning curve and preparation time, but in the end all the changes and deployment of the application would be done automatically, this resulted in maximized focus on the development of the application rather than reflecting the changes later on. Other than that, GitOps itself is not limited to Containerized Infrastructure, although since GitOps is designed with virtualization in mind, theoretically, the efficiency would be reduced if it’s implemented in other kind of IT Infrastructure